A Cross-sectional Histo-morphological Study of Vesiculobullous Lesions of Skin - Kr Tiwari, Amit; Sharma, Swati; K. Mathur, Deepak (International Journal of Medical Research and Review, 2016)
Histopathology study of skin biopsies is one of the useful techniques in the investigation of vesiculobullous lesions. Out of the 70 cases of vesicobullous studied, pemphigus vulgaris was the most common type with 44 cases (61.4%) which is followed by 25 cases (35.7%) of pemphigus foliaceus and least percent was found with 1 cases (2.9%) for pemphigus vegetans. Case study showed that disease was predominately observed in male in the ratio of 1.4:1 (25 males and 18 females). It was observed in Pemphigus vulgaris cases that initial lesions involves mucous membranes in 37.2% cases and 13.9% cases involves lesions including both skin and mucosae in 13.9% cases. Mucosal involvement at one time or the other was seen in 31 patients (72.1 %). In despite of this, in pemphigus foliaceus, only 4% cases showed initial mucosal involvement and involvement of both skin and mucous membrane was observed in 12% cases. This establishes that along with clinical correlation, histo-morphological study is also a important tool in the diagnosis of Vesiculobullous skin disorders.